Non-disclosure to male partners and incomplete PMTCT regimens associated with higher risk of mother-to-child HIV transmission: a national survey in Kenya. Issue 6 (3rd June 2018) - McGrath, Christine J.; Singa, Benson; Langat, Agnes; Kinuthia, John; Ronen, Keshet; Omolo, Danvers; Odongo, Benjamin Elly; Wafula, Rose; Muange, Prisca; Katana, Abraham; Ng'anga', Lucy; John-Stewart, Grace C.
ABSTRACT: Health worker experience and community support may be higher in high HIV prevalence regions than low prevalence regions, leading to improved prevention of mother-to-child HIV transmission (PMTCT) programs. We evaluated 6-week and 9-month infant HIV transmission risk (TR) in a high prevalence region and nationally. Population-proportionate-to-size sampling was used to select 141 clinics in Kenya, and mobile teams surveyed mother-infant pairs attending 6-week and 9-month immunizations. HIV DNA testing was performed on HIV-exposed infants. Among 2521 mother-infant pairs surveyed nationally, 2423 (94.7%) reported HIV testing in pregnancy or prior diagnosis, of whom 200 (7.4%) were HIV-infected and 188 infants underwent HIV testing. TR was 8.8% (4.0%–18.3%) in 6-week and 8.9% (3.2%–22.2%) in 9-month cohorts including mothers with HIV diagnosed postpartum, of which 53% of infant infections were due to previously undiagnosed mothers. Of 276 HIV-exposed infants in the Nyanza survey, TR was 1.4% (0.4%–5.3%) at 6-week and 5.1% (2.5%–9.9%) at 9-months. Overall TR was lower in Nyanza, high HIV region, than nationally (3.3% vs. 7.2%, P  = 0.02). HIV non-disclosure to male partners and incomplete ARVs were associated with TR in both surveys [aOR = 12.8 (3.0–54.3); aOR = 5.6 (1.2–27.4); aOR = 4.5 (1.0–20.0), aOR = 2.5, (0.8–8.4), respectively]. TR was lower in a high HIV prevalence region which had better ARV completion and partner HIV disclosure, possibly due to programmatic efficiencies or community/peer/partner support. Most 9-month infections were among infants of mothers without prior HIV diagnosis. Strategies to detect incident or undiagnosed maternal infections will be important to achieve PMTCT.